ANALYSIS OF STOCK AND UTILIZATION RATE OF LONGTAIL TUNA (Thunnus tonggol) IN THE JAVA SEA - Eki Septiana; Suradi Wijaya Saputra; Haeruddin Haeruddin (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2021)
Longtail is one of the most important economic species in Indonesia to purse seine and mini purse seine catch. This research activity aims to determine population parameter i.e. growth, mortality, and determine the management strategies for longtail tuna. The collecting of length and weight data was conducted at Pekalongan fishing port from October to December 2019. The sampling method used was a systematic random sampling method, with the collected data being the length and weight of the longtail tuna. The long weight r relationship was negative allometric and the b value was 2.7776. The asymptotic length rate (L∞) was 55 cm FL, growth rate (K) was 0,88/year and zero age (t0) was 0,1536 year. Natural mortality (M) is 1.41/year, fishing mortality (F) is 1.38/year, total mortality (Z) is 2.79/year. The level of exploitation (E) of 0.49 (underexploited), so that utilization can be increased.